DETERMINATION OF THERMAL ENERGY AND WASTES GENERATION RESULTING FROM INCINERATION OF ONE TON OF CRUDE OIL CONTAMINATED SOILS OF QURNA OIL FIELDS IN BASRA, IRAQ - Hadi, Ahmed H.; Ahmed, Ahmed Hatif; Hussain, Basim A.; Abd AL Razak, Abdullah F. (International Journal of Engineering Science Technologies, 2024)
A theoretical study is presented to calculate the thermal energy and wastes generated from complete combustion of (1 ton/h) of Qurna crude oil contaminated soil in Basra city south of Iraq. Practical values which are valid in the literature are taken for the constituents of the soil and the crude oil. A multi chamber incinerator with capacity of (1 ton/h) is designed to incinerate the crude oil contaminated soils using diesel fuel to reach to (1200˚C) burning temperature. The resulted thermal energy was found to be (5.59 MW) which is sufficient to evaporate (9918.449 liter/h) of industrial wasted water using many of Shore VAP water evaporators systems. The resulting hazardous flue gases and wastes obtained were (CO2=1773.46 kg/h, SO2 = 13.58kg/h, H2SO4 =0.643125kg/h (350 ml/h)) using excess air ratios of 150% for solid wastes burning and 20% for diesel fuel burning.